Biomonitoring of airborne fluoride and polycyclic aromatic hydrocarbons in industrial areas of Cordoba, Argentina, using standardized grass cultures of Lolium multiflorum - Rodriguez, Judith Hebelen (2015)
A biomonitoring study was performed employing standardized grass cultures. Plants of Lolium multiflorum were exposed at 4 industrial sites over three?month periods in two seasons (dry and rainy) and the biomass produced was used for subsequent measurements of fluoride, polycyclic aromatic hydrocarbons (phenanthrene, anthracene, pyrene, benzo[a]anthracene, chrysene, benzo[b]fluoranthene, benzo[k]fluoranthene, benzo[a]pyrene, dibenzo[a,h]‐ anthracene and benzo[g,h,i]perylene), total chlorophyll, malondialdehyde, water, and sulfur content. The total content of polycyclic aromatic hydrocarbons (PAHs) revealed seasonal variations, with the highest values corresponding to the dry season, although this species showed a high retention capacity of PAHs during rainy season. In addition, sampling sites with high vehicular traffic and metal?mechanical industries were associated with the highest content of PAHs. Furthermore, physiological degradation associated with anthropogenic activities in the sampling sites was observed. Fluoride content in the biomonitor was associated with the production and use ofcement, which was higher in the dry season.